First Light And Reionization Epoch Simulations (FLARES) -- II: The photometric properties of high-redshift galaxies. Issue 3 (30th November 2020) - Vijayan, Aswin P; Lovell, Christopher C; Wilkins, Stephen M; Thomas, Peter A; Barnes, David J; Irodotou, Dimitrios; Kuusisto, Jussi; Roper, William J
ABSTRACT: We present the photometric properties of galaxies in the First Light And Reionization Epoch Simulations (FLARES). The simulations trace the evolution of galaxies in a range of overdensities through the epoch of reionization. With a novel weighting scheme, we combine these overdensities, extending significantly the dynamic range of observed composite distribution functions compared to periodic simulation boxes. FLARES predicts a significantly larger number of intrinsically bright galaxies, which can be explained through a simple model linking dust attenuation to the metal content of the interstellar medium, using a line-of-sight extinction model. With this model, we present the photometric properties of the FLARES galaxies for z ∈ [5, 10]. We show that the ultraviolet (UV) luminosity function (LF) matches the observations at all redshifts. The function is fitted by Schechter and double power-law forms, with the latter being favoured at these redshifts by the FLARES composite UV LF. We also present predictions for the UV-continuum slope as well as the attenuation in the UV. The impact of environment on the UV LF is also explored, with the brightest galaxies forming in the densest environments. We then present the line luminosity and equivalent widths of some prominent nebular emission lines arising from the galaxies, finding rough agreement with available observations. We also look at the relative contribution of obscured and unobscured star formation, finding comparable contributions at these redshifts.